Why do women leave surgical training? A qualitative and feminist study. Issue 10171 (9th February 2019) - Liang, Rhea; Dornan, Tim; Nestel, Debra
Summary: Background: Women are under-represented in surgery and leave training in higher proportions than men. Studies in this area are without a feminist lens and predominantly use quantitative methods not well suited to the complexity of the problem. Methods: In this qualitative study, a researcher interviewed women who had chosen to leave surgical training. Women were recruited using a purposive snowball strategy through the routine communications of the Royal Australasian College of Surgeons and Royal Australasian College of Surgeons Trainee Association over a 3-week period, and were interviewed over the following 4 months in the past 4 years in person or by telephone. More specific details are available on request from the authors. Supported by male and female co-researchers, and in dialogue with study participants, she then coded the findings and defined themes. An explanatory model was developed by integrating findings with different theories and previous literature. The research team developed three aspects of the model into a visual analogue. Findings: 12 women participated in the study, with all Australian states and territories, and New Zealand, as well as five medical specialty streams, represented. The time spent in training ranged from 6 months to 4 years, and all participants, except two, had trained in both metropolitan and rural locations. The findings confirmed factors identified in earlier reports as reasons women leave surgical training, and contributed six new factors: unavailability of leave, a distinction between valid and invalid reasons for leave, poor mental health, absence of interactions with the women in surgery section of their professional body and other supports, fear of repercussion, and lack of pathways for independent and specific support. The relationships between factors was complex and sometimes paradoxical. The visual analogue is a tower of blocks, with each block representing a factor that contributed to the decision to leave surgical training, and with the toppling of the tower representing the choice to leave. The visual analogue indicates that effective action requires attention to the contributory factors, the small actions that can topple the tower, and the contexts in which the blocks are stacked. Interpretation: Women might be best helped by interventions that are alert to the possibility of unplanned negative effects, do not unduly focus on gender, and address multiple factors. This should inform interventions in surgical training, with attention to local social context, health-care setting, and training programme structure. Funding: Royal Australasian College of Surgeons Ian and Ruth Gough Surgical Education Scholarship.